RESEARCHING THE GEOMETRIC LIMITS OF 3D LASER SCANNING - Sarka, Ferenc; Malik, András (Design of Machines and Structures, 2024)
The paper presents the geometrical properties of those surfaces that can be digitized by 3D laser scanners. First the circumstances of the experiment are described. The device (Roland LPX-1200) and applied software (Dr. Pizza) are also introduced, such as the brief historical development of 3D digitization. Based on the data found in the literature, all those problems are collected, that can emerge during 3D laser scanning. In order to find the limits of the scanner, a test specimen was designed with a variety of geometric elements (planes in different positions, curved surfaces (concave, convex), roundings and chamfers in different sizes and positions, holes of different depths and diameter). During the design of the test specimen, those properties that were developed for additive technologies were used. The test specimen was produced by milling technology (Roland MDX 650), and then scanning with different settings were performed on it. The experiment was carried out until the largest real surface was digitized. Based on the test, it was summarized which geometries can be fully or partially scanned. Finally, a recommendation to achieve the best possible result was formulated.